The Impact of Oil Price Shocks on Growth and Inflation of OPEC Countries with an Emphasis on OPEC Political Risk Shocks - Ali Takroosta; Parisa Mohajeri; Teymour Mohamadi; Abbas Shakeri (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2019)
Considering the source of oil shocks, this study aims to investigate the effect of oil price shocks on the key macroeconomic variables of the OPEC countries. Even though oil shocks are originated by various factors, political risks are of great importance. Using structural vector-autoregressive model, we disentangled oil shocks and studied their impacts on OPEC’s GDP growth and inflation, using a Panel-VAR for 1994:1-2016:4. Our results highlight that among oil shocks, the oil price shocks stemming from the political risk of OPEC countries have the most significant impact on the OPEC's economic growth, while not having any significant impact on inflation of the countries. We also learned that oil supply shocks could also boost economic growth and increase inflation rates in OPEC countries, although these increases are not significant. Other oil price shocks will only lead to higher inflation in these countries without affecting OPEC's economic growth.